ANALISIS KANDUNGAN ZAT GIZI BROWNIES TEMPE SUBTITUSI WORTEL (Daucus carota L.) SEBAGAI ALTERNATIF PERBAIKAN GIZI TERHADAP MASYARAKAT - A. Ibrahim, Irviani; Ibrahim, Hasbi; Isma, Rabiatul (Media Gizi Pangan, 2017)
Backgrounds: Brownies are popular food and favored by many people at different ages, including school-age children. In this study, the raw materials used in the brownies are tempe and carrot (Daucus carota L), both materials have a high content of nutrients including iron and vitamin A.Objectives: The study aims to determine the nutrients contents (carbohydrates, protein, fat, vitamin A and fe) and the organoleptic testing of the products of tempe brownies of carrot (Daucus carota L.) subtitution.Methods: The study is a true-experimental research using a completed randomized design (CRD). The results revealed that 4 treatments with different concentrations by adding carrot (Daucus carota L.) are 1:0  (100g tempe), 3:1 (75g tempe, 25g carrot), 1:1 (50g tempe, 50g carrot) and 1:3 (25g tempe, 75g carrot) with three rehashes.Results: The results of Carbohydrates research of 13.78%, protein 11.52%, fat 24.29%, vitamin A 5,17ug/g, iron 36,89ug/g. The organoleptic testing that most preferred and good quality is 1:1 treatment. The Friedman testing of P<0.05 is on scent, taste and the overall quality.Conclusions: The 1:1 ratio is the best product recommendation based on the nutrients and organoleptic testing of four samples.                                        Keywords: Brownies, Tempe, Carrot (Daucus Carota L.), Nutrient